SOSIALISASI CiPOM (CEK KLIKK BPOM) KOSMETIK PADA SISWA SISWI SMA NEGERI 4 JEMBER - Tanfidz Alishlah; Evi Umayah Ulfa; Indah Yulia Ningsih (Jurnal Hasil Pengabdian kepada Masyarakat Universitas Jember, 2022)
Indonesia's cosmetics industry is currently very rapidly growing. Along with the increasing cosmetics market in Indonesia, more people are also taking advantage by producing illegal cosmetics containing harmful ingredients that are very detrimental to consumers. Based on data, 70% of consumers who use cosmetics in Indonesia are teenagers. Teenagers have low knowledge of the safety of cosmetic products. One of the efforts is the socialization of CiPOM, checking KLIKK (Packaging, Labels, Distribution Permits, Uses, and Expirations) BPOM on cosmetics. This activity aims to increase public education among teenagers about cosmetics. This method of service activities uses the method of online lectures and discussions using Zoom meeting. The participants of this activity are Grade 2 students of SMA Negeri 4 Jember. The participant post-test results were 90% of the total participants scored ≥ 70, and the accuracy average score increased from 38.4% during the pre-test to 75.5% during the post-test which showed that participants understood the socialization material that had been delivered. This community service activity can be said to be successful, judging from the indicators of success that have been achieved, attendance rate, and activity of participants. This activity is expected to continue to be carried out regularly considering the low level of knowledge of teenagers as consumers of cosmetic products. The existence of this community service activity is expected to be able to provide understanding, knowledge, and participants can apply and disseminate information to choose safe cosmetics.